2017
DOI: 10.3390/ijms18102184
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as a Novel Regulator of Tumor Metabolism: Insights on Potential Mechanisms and Implications for Anti-Cancer Therapy

Abstract: 1,25-dihydroxyvitamin D3 [1,25(OH)2D3], the bioactive form of vitamin D, has been shown to possess significant anti-tumor potential. While most studies so far have focused on the ability of this molecule to influence the proliferation and apoptosis of cancer cells, more recent data indicate that 1,25(OH)2D3 also impacts energy utilization in tumor cells. In this article, we summarize and review the evidence that demonstrates the targeting of metabolic aberrations in cancers by 1,25(OH)2D3, and highlight potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 69 publications
1
23
0
1
Order By: Relevance
“…N-Myc is a member of the Myc transcription factor family that acts as a proto-oncogene and has been reported to be overexpressed in colorectal cancer [ 37 , 38 ]. Interestingly, other members of the Myc family have been implicated as being responsible for the metabolic programing of colorectal cancer [ 39 ], and when this pathway is downregulated, cancer metabolism is altered [ 40 ]. Our data show that when RCC and LCC were treated with calcitriol, the Myc pathway was downregulated, thus presumably causing changes in metabolism in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-Myc is a member of the Myc transcription factor family that acts as a proto-oncogene and has been reported to be overexpressed in colorectal cancer [ 37 , 38 ]. Interestingly, other members of the Myc family have been implicated as being responsible for the metabolic programing of colorectal cancer [ 39 ], and when this pathway is downregulated, cancer metabolism is altered [ 40 ]. Our data show that when RCC and LCC were treated with calcitriol, the Myc pathway was downregulated, thus presumably causing changes in metabolism in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Calcitriol supplementation has been reported to cause changes in cancer metabolism primarily through the reduction of Myc [ 39 , 40 ]. Our results from both proteomic and metabolomic studies of calcitriol treatment in LCC and RCC indicate that these changes in metabolic pathways are happening in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that calcitriol takes part in numerous physiological processes, including enhancement of proliferation and differentiation of immune cells ( 52 , 53 ). It induces apoptosis of neoplastic cells and inhibits their multiplication ( 52 , 53 ), increases production of cathelicidin and beta-defensin ( 51 , 54 56 ), modulates lymphocyte activity ( 51 ), Th1 and Th2 lymphocyte ratio ( 51 , 57 ), decreases concentrations of proinflammatory cytokines (IL-1, TNFα), simultaneously increasing anti-inflammatory cytokines (IL-4, IL-5 and IL-10) ( 51 , 58 ), decreases renin secretion and in this way reduces activity of the renin–angiotensin–aldosteron system ( 59 , 60 ), inhibits angiogenesis ( 61 63 ), and has favorable effect on calcification processes in blood vessels ( 64 67 ), stimulates synthesis of neurotrophic factors ( 68 , 69 ) and inhibits fibrosis in kidneys ( 70 , 71 ). Vitamin D deficiency decreases insulin secretion ( 72 ).…”
Section: Evidence Base For Updated Polish Recommendationsmentioning
confidence: 99%
“…Upon binding to its receptor, 1,25(OH) 2 D 3 induces immense changes in gene expression patterns in different cells, with several genes identified as either direct—harboring vitamin D response elements (VDRE)—or indirect targets of the molecule. Such genes include those involved in the regulation of proliferation, such as p21 and p27, apoptosis-related genes, like BAX, and tissue-specific differentiation genes, such as prostate specific antigen [ 1 , 2 , 3 ]. Among the putative vitamin D target genes is thioredoxin-interacting protein (TXNIP), which is located on chromosome 1q21.1.…”
Section: Introductionmentioning
confidence: 99%